AN ANTIHERO IN THE SPACE OF A SOUTH KOREAN DRAMA: IS IT OKAY TO NOT BE OKAY? / АНТИГЕРОЙ В ПРОСТРАНСТВЕ ЮЖНОКОРЕЙСКОГО СЕРИАЛА: НОРМАЛЬНО ЛИ БЫТЬ НЕНОРМАЛЬНЫМ? - Tarasova Aleksandra V. / Тарасова А.В. (Наука телевидения, 2021)
The article focuses on the image of an antihero in South Korean television series: its typical features, its functions, and interaction with the audience. The article opens with a brief outline of the antihero version that has been sought after by the global audience since the 2000s—a gifted sociopath, unable and unwilling to maintain the generally accepted format of interaction with other people. Further, the article turns to the historical and cultural conditions in which such antiheroes find themselves in the South Korean TV series. First of all, there are the principles of Confucian ideology: the priority of society over an individual, reverence for elders, drive to maintaining family ties, strict adherence to etiquette. This ideology, combined with the South Korean television’s tendency to be didactic, seems to create an unfavorable environment for antiheroes. However, the following three South Korean dramas—Kill Me, Heal Me (2015), A Beautiful Mind (2016), and It’s Okay to Not Be Okay (2020)—show that a character with recognizable antihero traits may successfully fit into the structure of these narratives. And since the antihero function in the third series is performed by the main female character, her behavior conflicts not only with Confucian norms, but also with stereotypical behavior patterns of female characters in South Korean TV series. However, the results of the study suggest that, in general, a South-Korean-type antihero is created under the influence of Confucian ethics. Society and family play an important role both in the formation of the antihero’s personality and in his or her subsequent “normalization”. Besides, the image of a South Korean antihero may indicate a more tolerant attitude of contemporary South Korean society towards the non-standard lifestyles and behavior of the individuals. Статья посвящена образу антигероя в телесериалах Южной Кореи — его характерным чертам и функциям, которые такой персонаж исполняет в сюжете сериала и во взаимодействии со зрительской аудиторией. Открывает статью описание версии антигероя, востребованной у глобальной аудитории с 2000-х гг. — одаренного социопата, не умеющего и не желающего поддерживать общепринятый формат взаимодействия с другими людьми. Далее статья обращается к историко-культурным условиям, в которые подобный антигерой попадает в сериале корейском. В первую очередь это принципы конфуцианской идеологии: приоритет общества перед отдельной личностью, почитание старших, поддержание родственных связей, строгое соблюдение правил этикета. Подобная идеология в сочетании со склонностью корейского телевидения к дидактике формирует неблагоприятные условия для антигероя. Однако далее на примере трех корейских сериалов — «Убей меня, исцели меня» (2015), «Блестящего ума» (2016) и «Это нормально — быть ненормальным» (2020) — демонстрируется, что персонаж, обладающий узнаваемыми признаками антигероя, успешно вписывается в структуру этих повествований. А поскольку функцию антигероя в третьем из сериалов исполняет главная героиня, ее поведение вступает в противоречие не только с конфуцианскими нормами, но и со стереотипными моделями поведения женских персонажей корейских сериалов. Однако результаты исследования позволяют предположить, что в целом антигерой корейского образца создается под воздействием конфуцианской этики. Общество и семья играют большую роль как в формировании личности антигероя, так и в его последующей «нормализации». Кроме того, образ корейского антигероя может свидетельствовать о более терпимом отношении современного корейского общества к нестандартному образу жизни и поведению индивида.